Morocco : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper analyzes the recent developments in the Moroccan economy and its policy challenges over the medium term. It assesses the sustainability of public debt in Morocco. The paper uses the analytical framework for assessing debt sustainability in emerging market countries endorsed by the IMF Executive Board and compares Morocco's vulnerabilities with those of the average emerging market country. The paper also examines the effects on Morocco's trade pattern of the ongoing integration with the European Union within the Barcelona process.